Participatory Planning of Tourist Train Station Accessibility and Creative Industry Development - Muhamad, Muhamad; Rahmawati, Aneke (E-Journal of Tourism, 2021)
Wirun tourism village, which covers an area of 265,500 ha, is an area that has its appeal in the creative industry with its strategic location which is located on the main transportation route and is traversed by bus routes that are widely used by people for transportation. There is alternative transportation in the form of Tourist Trains for the people to expand their reach but they are only able to pass by and overlook the area. The purpose of this study is to determine the process of participatory planning that has high acceptability if implemented. This is because all of the stakeholders are involved in every stage of planning policy formulation. The developed method aims to describe, explain and validate social phenomena as the object of the research by systematically creating descriptions, portrayals or paintings, as well as relationships between the observed phenomena and a process or relationship, providing a complete picture in either verbal or numerical form, presenting basic information of a relationship, creating a set of categories and classifying the research subjects. The results of this study are the concept of participatory planning in the development of the concept of reconstruction, adaptive revitalization in connecting tourist destinations with the gamelan creative industry through spatial and regional revitalization approaches.